HUMANISM IN TIMES OF PANDEMIC: ONLINE CLINICAL SIMULATION FOR THE DEVELOPMENT OF ETHICAL COMPETENCIES (Proceedings of the International Conference on Education, 2021)
The SARS-COV2 health contingency and the cessation of face-to-face activities has motivated multiple educational innovations for distance teaching. Medical schools are particularly defied because of the need for clinical training, however simulation offers opportunities to achieve continuity. A clinical simulation exercise was redesigned and transformed to an online synchronic simulation via Zoom. The participating groups of medical students (n=53) were in the Bioethics and Clinical Bioethics courses, adjunct to their Pediatrics and Obstetrics and Gynecology (ObGyn) clerkships in June 2020. Two simulated clinical cases were performed via Zoom, followed by a debriefing session. Later, an online survey was applied to the participants to know their perception and experience with this new version, considering they had experienced the original face-to-face simulation on the alternate clerkship the prior trimester. A mixed method approach was used to analyze the responses. The results showed that the virtual format was very effective, 72% considered it very similar to the original version. The exercise revealed high emotional commitment, allowing students to develop their socio-emotional skills. Student reactions were categorized and coded as emotions triggered by a) their performance as professionals, b) those related directly to the patient’s emotions and situation, which showed significant gender differences, and c) students'  anxiety related to the academic exercise itself, the least found. The fact that the clinical component was restructured due to the remote format may have helped in focusing on the preponderance of emotional, communication and relational aspects of the patient-doctor relationship. Also, most students identified the exercise was meaningful in approaching bioethics contents, including end-of-life decisions in patient care, and informed consent. In conclusion, the online clinical simulation activity proved effective in integrating professionalism outcomes that encompass ethical knowledge, skills and attitudes that prepare medical students for their professional role, along with the debriefing reinforcing insightful learning integration.
Keywords: educational innovation; higher education; clinical simulation; humanism; ethics